Comparing Associations Between Puberty, Ethnic–Racial Identity, Self‐Concept, and Depressive Symptoms Among African American and Caribbean Black Boys. Issue 6 (5th May 2020) - Carter, Rona; Seaton, Eleanor K.; Blazek, Janelle L.
Abstract : Research on pubertal development among Black boys is limited. Addressing this gap, we examined associations between three pubertal domains (e.g., voice change, hair growth, and perceived relative timing), depressive symptoms, self‐esteem, and self‐efficacy, among a nationally representative sample of 395 African American and 164 Caribbean Black boys ( M age  = 15 years). Moderation by ethnic–racial identity (e.g., racial centrality, racial regard) was also explored. Results indicated that for both ethnic subgroups early voice change increased self‐esteem; whereas early voice change increased depressive symptoms among boys who felt society views Blacks more negatively. Buffering effects of ethnic–racial identity also varied significantly between the two groups. Findings suggest that the meaning Black boys ascribe to their ethnic–racial group may explain puberty‐linked outcomes.